Terahertz Semiconductor Dual‐Comb Sources with Relative Offset Frequency Cancellation (Laser Photonics Rev. 17(4)/2023). Issue 4 (7th April 2023) - Li, Ziping; Ma, Xuhong; Zhou, Kang; Liu, Binbin; Wang, Chenjie; Liao, Xiaoyu; Guan, Wen; Wu, Shumin; Liu, Han; Zhang, Zhenzhen; Cao, J. C.; Li, Min; et al.
Abstract : Terahertz Semiconductor Dual‐Comb Sources with Relative Offset Frequency Cancellation In article number 2200418, J.C. Cao, Heping Zeng, Hua Li, and colleagues present a self‐reference approach to improve the stability of terahertz semiconductor‐based quantum cascade laser dual‐comb sources. The proposed method can entirely remove the common dual‐comb carrier offset frequency noise and then significantly improve the long‐term stability of the dual‐comb sources emitting in the terahertz frequency range. The self‐referenced dual‐comb sources show potentials for spectroscopic applications.